Evaluasi Kinerja dengan Pendekatan Balanced Scorecard di Poliklinik Unit Rawat Jalan RSUD Andi Djemma Masamba, Sulawesi Selatan - Santika, Made; Yuliaty, Farida; Wirawan, Chevie (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Balanced scorecards are often used in various organizations, including hospitals, because they are able to measure performance in a comprehensive, consistent, measurable and balanced manner. Until now, performance measurement in the outpatient clinic of Andi Djemma Regional Hospital still focuses on financial aspects only. This research aims to analyze polyclinic performance using the balanced scorecard method through four main perspectives: finance, customers, internal business processes, and growth and learning. The research method applied is a quantitative descriptive approach. Performance data was collected from hospital secondary data for 2023 and previously, as well as primary data through questionnaires involving patients and employees. The results of the analysis show that performance from a financial and customer perspective is classified as